Risk behaviours for HIV infection among drug users in prison. - Carvell, A L (1990)
OBJECTIVE--To study a group of injecting drug users to establish the degree of illicit drug use in prisons, the prevalence of risk behaviours for HIV infection, and the uptake of treatment for drug dependency with drugs within the prison system. DESIGN--Anonymous, self administered, questionnaire. SETTING--Two drug agencies in central London; one operating a scheme for exchanging needles, and the other offering drug advice and information. SUBJECTS--50 (42 Men, eight women) self selected injecting drug users (mean age 31.2 (range 21-42)), all of whom had been held in custody at some time since 1982. MAIN OUTCOME MEASURES--Details about periods served in custody since 1982; the number of respondents who took drugs (orally or by injection), either illicitly or prescribed, while in prison and the types of substances taken; the respondents' sexual activity in prison and between periods in custody. RESULTS--The average time spent in custody before the study was 20.6 months (range 1-72). Most prosecutions were directly or indirectly related to drug taking. 47 Of the 50 respondents reported taking at least one illicit drug while in custody; 33 by injection, 26 of whom had shared injecting equipment. 30 Had been treated for drug dependency by the prescribing of drugs while in prison. While in custody, one woman and four men (with a mean of seven (range 2-16) male partners) had had sex. Between periods spent in custody, men reported having a mean of eight (range 0-90) female partners and women a mean of one (range 0-3) male partner. Three men had had sex with other men, with a mean of six (range 2-11) partners. Since their last period in custody, men had had a mean of two (range 0-18) female partners and women had had a mean of two (range 1-3) male partners. Five men had also had male partners. CONCLUSIONS--A high prevalence of injecting and sexual risk behaviours among injecting drug users within and between periods in custody has been shown. Most of these offenders continued to take drugs while in custody, and just over half not only injected drugs but shared equipment. Some of the male prisoners compounded their risk of HIV infection by engaging in sexual activity with multiple partners. Prisoners who then have multiple sexual partners after release place their partners in the community at particular risk of HIV infection. Although many of the drug users were prescribed drugs for their dependency, limited access to appropriate treatment, counselling, and health education may compound the situation.